Strategi pemasaran klaster lobster dan ikan kerapu berbasis teknologi E-commerce di Kepulauan Barrang Caddi - Abd. Rahman Patta; Hasrul Bakri; Suharto Suharto (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The purpose of this activity were 1) farmerscultivating lobster and grouper can apply transfer paymentmodels are supported with the features of the e-commerceapplication; 2) utilize the application e-commerce farmerscultivating lobster and grouper so it can be more efficient andeffective in increasing the farmers income through servicesand results; 3) the availability of information on production,services and prices of lobster and groupers in real time can beaccessed by hotel, restaurant, supermarket, local buyers, localbusinessmen, and exporters; 4) to form broader communitiesof lobster and grouper sellers. The methods used in thisCommunity Partnership program covered discussions, lectures,demonstrations, simulations and evaluations. The outputtargets in this program were 1) E-commerce applicationmanagement training for lobster marketing and lobster exports;2) Lobster Farmers and Grouper Farmers can provide Lobsterand Fish Shipping Services (JPLI) from sea to land using boatsat certain rates; 3) Lobster and Grouper Farmers can be theservice providers for entrepreneurs; 4) Ordering andpurchasing lobsters and groupers by hotel, restaurant, andsupermarket entrepreneurs, local buyers, local collectors, andexporters can be directly to lobster cultivation farmers throughe-commerce; 5) Hotel businessmen, restaurants, andsupermarkets, local buyers, collectors local, and exporters canorder lobsters and groupers before harvest through ecommerce;6) Lobster and grouper cultivation can determinethe Minimum Price of Lobster and Grouper Auction (HMLB)to hotel, restaurant and supermarket entrepreneurs, localbuyers, local collectors, and exporters through e-commerceapplications; and 6) Farmers Aquaculture Lobster and groupercan cooperate to hotel businessmen, restaurants andsupermarkets, local buyers, local collectors and exportersthrough e-commerce applications.